2014
DOI: 10.1177/0022034514555144
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Severe Pain after Root Canal Therapy in the National Dental PBRN

Abstract: Some patients experience severe pain following root canal therapy (RCT) despite advancements in care. We sought to identify factors, which can be measured preoperatively, that predict this negative outcome so that future research may focus on preemptive steps to reduce postoperative pain intensity. Sixty-two practitioners (46 general dentists and 16 endodontists) who are members of the National Dental Practice-Based Research Network enrolled patients receiving RCT for this prospective observational study. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
81
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 28 publications
(54 reference statements)
10
81
2
1
Order By: Relevance
“…The results from this present study are consistent with the findings of Law [29] that to avoid severe postoperative pain in endodontic therapy, preemptive analgesia strategies before initiation of treatment are necessary and with Krasner & Jackson [31] who noted from their study that although pulpectomy eliminates endodontic pain, postoperative pain and discomfort. Two previous investigations have reported that the prophylactic use of analgesics at the end of the treatment visit had a positive influence on postoperative pain felt by the patients [10,32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results from this present study are consistent with the findings of Law [29] that to avoid severe postoperative pain in endodontic therapy, preemptive analgesia strategies before initiation of treatment are necessary and with Krasner & Jackson [31] who noted from their study that although pulpectomy eliminates endodontic pain, postoperative pain and discomfort. Two previous investigations have reported that the prophylactic use of analgesics at the end of the treatment visit had a positive influence on postoperative pain felt by the patients [10,32].…”
Section: Discussionsupporting
confidence: 92%
“…Know those factors as predictors may contribute to define preventive oral health strategies to manage this undesirable condition, minimizing pain incidence and/or intensity and reducing patient suffering at the individual and population levels. Additionally, clinicians may use this information to advise patients about pain outcomes related to RCT [29]. The results of the present study indicated that some clinicians were more likely to choose medication before and after endodontic treatment to manage this painful clinical scenario, whereas other educators and residents were much more likely to prescribe combination drugs in addition to instrumentation [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, acute postoperative pain and trismus after third molar extraction did not differ by gender (n ¼ 150, n ¼ 100) [44,45]. Accordingly, gender could not predict acute pain after root canal therapy (n ¼ 708) [46], although acute pain events were reported more often in women; however, without statistical significance (n ¼ 140) [47]. Interestingly, in a large retrospective cohort study with 1671 patients submitted to surgical correction of mandibular deformities, seven women and no men developed neuropathic pain that persisted for a median of 52 days, suggesting that women are at higher risk for neuropathic pain after mandibular surgery [48].…”
Section: Oral Surgerymentioning
confidence: 94%
“…For this, a simple 1-to-10 VAS was used in the feedback evaluation, where 1 represented the ‘least possible discomfort’ and 10 represented the ‘greatest possible discomfort.’ This scale has been used in several clinical studies evaluating postoperative pain. Moreover, there is considerable evidence indicating that the VAS has advantages over other methods in terms of feasibility and reliability 101112…”
Section: Discussionmentioning
confidence: 99%